USING AN AUTHENTIC AND SELECTED FILM FOR TEACHING LISTENING AND SPEAKING - Wienny Ardriyati (Dinamika Bahasa dan Budaya, 2010)
It is said that students become motivated about language learning, especially listening and speaking practices, when an authentic film is involved. Films can be valuable classroom tools if they show interesting and authentic scenarios in which relevant English is used. Effective films can take students' attention. In this article the selected film chosen is the animated Titanic. It is intended that the students can practice listening and speaking by watching and listening the film which uses of the verbal and non verbal communication. The language teacher uses three activities of teaching; pre-viewing, viewing and post-viewing. He/she asks the students to conclude and retell the story in chain.   Key words: authentic, non verbal communication (NVC), pre-viewing, viewing, post viewing activities, in chain